65. ICT-based Distance Education in South Asia - Berman, Sally D. (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2008)
This report provides an update about innovative uses of information and communication technology (ICT) for distance education and training in South Asia. Particular focus is given to ICT initiatives in India, Sri Lanka, and Bhutan, at university level, and in non-formal interventions. Lessons learned from these countries are of value to any developing nation that wishes to address the improvement of educational and living standards of its people. The report stresses current uses of ICT serving the distance education needs of rural populations, and concludes that in all three countries the traditional media, including radio and TV, must play an important continuing role to ensure that education is accessible to the widest possible range of students.